2021
DOI: 10.3390/ijms22147518
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Soft Tissue Sarcoma Immunity: Targets for Immune Intervention

Abstract: Soft tissue sarcomas (STSs) are a family of rare malignant tumors encompassing more than 80 histologies. Current therapies for metastatic STS, a condition that affects roughly half of patients, have limited efficacy, making innovative therapeutic strategies urgently needed. From a molecular point of view, STSs can be classified as translocation-related and those with a heavily rearranged genotype. Although only the latter display an increased mutational burden, molecular profiles suggestive of an “immune hot” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…In particular, no alterations were detected in the expression of ALK, MTOR, KIT, PDGFRA, NTRK1, NTRK2, and NTRK3, which are the targets of crizotinib, everolimus, imatinib, and larotrectenib, respectively. These results are suggestive of the refractoriness of these diseases to several treatments currently used for the management of other STS histotypes (e.g., anthracyclines, trabectedin or immunotherapy [ 39 , 40 ]) and support the clinical observation of the limited availability of therapeutic options and poor outcome of adult RMS patients. The observed results prompted us to deepen the investigation of molecular features of RMS1 lesion through a larger RNA-seq panel.…”
Section: Discussionsupporting
confidence: 63%
“…In particular, no alterations were detected in the expression of ALK, MTOR, KIT, PDGFRA, NTRK1, NTRK2, and NTRK3, which are the targets of crizotinib, everolimus, imatinib, and larotrectenib, respectively. These results are suggestive of the refractoriness of these diseases to several treatments currently used for the management of other STS histotypes (e.g., anthracyclines, trabectedin or immunotherapy [ 39 , 40 ]) and support the clinical observation of the limited availability of therapeutic options and poor outcome of adult RMS patients. The observed results prompted us to deepen the investigation of molecular features of RMS1 lesion through a larger RNA-seq panel.…”
Section: Discussionsupporting
confidence: 63%
“…Although most targeted drugs were not approved to be used as the first-line therapy for CRC by FDA, some studies revealed that tyrosine kinase inhibitor (TKI), including bosutinib, imatinib, and sunitinib, could enhance the infiltration of cytotoxic and effector T cells, which would directly affect the efficacy of immunotherapy ( Roulleaux Dugage et al, 2021 ; Tazzari et al, 2021 ; Hirata et al, 2022 ). These studies revealed that the application of TKI might be positively related to the infiltration of pro-inflammation immune cells, which meant that the combination therapy of TKI and ICB might receive better efficacy than monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, patients with mutations in the RB1 tumor suppressor gene have a significantly increased incidence of STS [39]. Furthermore, structural activation of oncogenic signaling pathways caused by oncogene mutations negatively affects the TME by promoting intratumoral immune cell rejection or facilitating the recruitment of immunosuppressive cells [40]. However, the treatment of STS still lacks efficient methods.…”
Section: Discussionmentioning
confidence: 99%